Body Mass Index, Height, and Head and Neck Cancer Risk: The Japan Public Health Center-based Prospective Study - Seitaro Suzuki; Taiki Yamaji; Motoki Iwasaki; Manami Inoue; Shoichiro Tsugane; Tomohiro Shinozaki; Norie Sawada (Journal of Epidemiology)
Background: Although both a lower and a higher body mass index (BMI) are reportedly associated with head and neck cancer (HNC), reports from Asia are scarce. Moreover, evidence regarding the association between height and HNC is limited. Methods: We investigated associations between BMI, height, and the incidence of HNC among 102,668 participants (49,029 men and 53,639 women) aged 40–69 years in the Japan Public Health Center-based Prospective Study. We followed participants from 1990 to 2013. We conducted a Cox proportional hazards regression analysis, which included adjustment for potential confounders, such as smoking status. Baseline weight and height information were self-reported. Results: Over an average follow-up of 18.7 years, 311 HNC cases were newly diagnosed. Lower BMI was significantly associated with HNC, with hazard ratios (HR) of 2.75 (95% confidence interval [CI], 1.63–4.64) for <18.5 kg/m2 and 1.63 (95% CI, 1.15–2.30) for 18.5–20.9 kg/m2 compared to 23–24.9 kg/m2. Increased risk was suggested for higher BMI, with an HR of 1.30 (95% CI, 0.84–2.00) for ≥27.5 kg/m2. This trend was also observed in quadratic models. Results were similar among never-smokers. Meanwhile, only lower BMI showed a strong association with HNC risk among former and current smokers (HR 3.09; 95% CI, 1.54–6.20 for <18.5 kg/m2 compared to 23–24.9 kg/m2). Height showed no association with HNC. Conclusion: Lower BMI was significantly associated with HNC risk, while increased HNC risk was suggested in higher BMI among never-smokers. Among former and current smokers, only lower BMI was associated with HNC risk.